Initial Boundary Value Problem and Asymptotic Stabilization of the Two-Component Camassa-Holm Equation - Xiju Zong; Xingong Cheng; Zhonghua Wang; Zhenlai Han (Abstract and Applied Analysis)
The nonhomogeneous initial boundary value problem for the two-component Camassa-Holm equation, which describes a generalized formulation for the shallow water wave equation, on an interval is investigated. A local in time existence theorem and a uniqueness result are achieved. Next by using the fixed-point technique, a result on the global asymptotic stabilization problem by means of a boundary feedback law is considered.